Cytotoxic potential of rhizome extracts of Hedychium spicatum L. in HepG2 cell line using MTT - CHOUDHARY, GOVIND KUMAR; SINGH, SATYA PAL (The Indian Journal of Animal Sciences, 2017)
The present study was designed to evaluate the cytotoxic effects of extract of Hedychium spicatum rhizome extract on human liver hepatocellular carcinoma (HepG2) cell line using MTT assay. The crude extract of H. spicatum was prepared by cold maceration method, filtered, concentrated in different organic solution and tested for phytochemical evaluation and finally on HepG2 cell line. Dose-dependent cytotoxic activities were exhibited on HepG2 cell line. As the dose of the extract increased, the number of viable cells decreased. This confirms the cytotoxic potential of the rhizome of H. spicatum. The IC50 value of different extracts was determined and concluded that the methanolic extract had better potential than the other extracts.